Can Individuals with Autism Abstract Prototypes of Natural Faces? - Gastgeb, Holly Zajac (2011)
There is a growing amount of evidence suggesting that individuals with autism have difficulty with face processing. One basic cognitive ability that may underlie face processing difficulties is the ability to abstract a prototype. The current study examined prototype formation with natural faces using eye-tracking in high-functioning adults with autism and matched controls. Individuals with autism were found to have significant difficulty forming prototypes of natural faces. The eye-tracking data did not reveal any between group differences in the general pattern of attention to the faces, indicating that these difficulties were not due to attentional factors. Results are consistent with previous studies that have found a deficit in prototype formation and extend these deficits to natural faces.